ORAL HEALTH KNOWLEDGE, ATTITUDE, AND PRACTICES OF MOTHERS OF PRESCHOOL CHILDREN TO VISITED AT THAI NGUYEN GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Describe mothers' knowledge, attitudes, and practices on oral health care for preschool children visiting Thai Nguyen General Hospital.Material and Methods: Cross-sectional descriptived study on 216 mothers with preschool children visiting Thai Nguyen General Hospital from March 2025 to September 2025, interviewed directly using a pre-designed questionnaire.Results: Most mothers are in the age group of 26-35 years old, accounting for 66.2%, Kinh ethnic group accounts for 75.0%, mothers working as civil servants account for 46.3%. The rate of mothers with correct knowledge about oral care for children is 23.6%. The rate of mothers with good attitudes about oral care for children is 68.5%. The rate of mothers who practice proper oral care for their children is 42.6%.Conclusion: Knowledge, attitudes and practices of mothers on oral health care for preschool children in our study are not high. Therefore, it is necessary to strengthen health education on oral hygiene in medical facilities and kindergartens. Provide clear instructions: time of brushing teeth, fluoride standards, time of first dental examination.
Keywords: Knowledge, attitudes, practices, oral care, children